Preoperative Management of Pheochromocytoma and Paraganglioma - Fang, Fang; Ding, Li; He, Qing; Liu, Ming (Frontiers in Endocrinology, 2020)
Pheochromocytoma and paraganglioma (PPGL) are rare neuroendocrine tumors, characterized by excessive release of catecholamines (CAs), and manifested as the classic triad of headaches, palpitations, profuse sweating, and a variety of other signs and symptoms. The diagnosis of PPGL requires both evidence of excessive release of CAs and anatomical localization of CA-secreting tumor. Surgery is the mainstay of treatment for all patients with PPGL unless contraindicated. However, without proper preparation, the release of excessive CAs, especially during surgery, can result in lethal cardiovascular complications. Herein, we briefly reviewed the pathogenesis of this disease, discussed the current approaches and evidence available for preoperative management, summarizing the results of the latest studies which compared the efficacies of preoperative management with or without α adrenergic-receptor antagonists, aiming to facilitate better understanding of the preoperative management of PPGL for the physicians.